Anal abnormalities in childhood myotonic dystrophy–a possible source of confusion in child sexual abuse. Issue 4 (April 1992) - Reardon, W; Hughes, H E; Green, S H; Lloyd Woolley, V; Harper, P S
Abstract : Myopathic involvement of the perianal musculature is one of the less well recognised features of myotonic dystrophy in children and may present with physical signs suggestive of sexual abuse. Details of six children with myotonic dystrophy are presented to emphasise the importance of considering an underlying myopathic condition in the differential diagnosis of anal laxity.